Hydroxyapatite from Mollusk Shells: Characteristics, Production, and Potential Applications in Dentistry - Florin Lucian Muntean; Iustin Olariu; Diana Marian; Teodora Olariu; Emanuela Lidia Petrescu; Tudor Olariu; George Andrei Drăghici (Dentistry Journal)
Modern dentistry is turning towards natural sources to overcome the immunological, toxicological, aesthetic, and durability drawbacks of synthetic materials. Among the first biomaterials used as endosseous dental implants, mollusk shells also display unique features, such as high mechanical strength, superior toughness, hierarchical architecture, and layered, microporous structure. This review focusses on hydroxyapatite—a bioactive, osteoconductive, calcium-based material crucial for bone healing and regeneration. Mollusk-derived hydroxyapatite is widely available, cost-effective, sustainable, and a low-impact biomaterial. Thermal treatment coupled with wet chemical precipitation and hydrothermal synthesis are the most common methods used for its recovery since they provide efficiency, scalability, and the ability to produce highly crystalline and pure resulting materials. Several factors, such as temperature, pH, and sintering parameters, modulate the size, purity, and crystallinity of the final product. Experimental and clinical data support that mollusk shell-derived hydroxyapatite and its carbonated derivatives, especially their nanocrystaline forms, display notable bioactivity, osteoconductivity, and osteoinductivity without causing adverse immune reactions. These biomaterials are therefore highly relevant for specific dental applications, such as bone graft substitutes or dental implant coatings. However, continued research and clinical validation is needed to optimize the synthesis of mollusk shell-derived hydroxyapatite and determine its applicability to regenerative dentistry and beyond.